DMS2015-33: Generative interface structure design for supporting existing objects. (December 2015) - Ulu, Nurcan Gecer; Kara, Levent Burak
Abstract: Increasing availability of high quality 3D printing devices and services now enable ordinary people to create, edit and repair products for their custom needs. However, an effective use of current 3D modeling and design software is still a challenge for most novice users. In this work, we introduce a new computational method to automatically generate an organic interface structure that allows existing objects to be statically supported within a prescribed physical environment. Taking the digital model of the environment and a set of points that the generated structure should touch as an input, our biologically inspired growth algorithm automatically produces a support structure that when physically fabricated helps keep the target object in the desired position and orientation. The proposed growth algorithm uses an attractor based form generation process based on the space colonization algorithm and introduces a novel target attractor concept. Moreover, obstacle avoidance, symmetrical growth, smoothing and sketch modification techniques have been developed to adapt the nature inspired growth algorithm into a design tool that is interactive with the design space. We present the details of our technique and illustrate its use on a collection of examples from different categories.